1

1

Let the total height be H_{1}.

Distance travelled: S = ut + at^{2}

Distance travelled in the first three seconds: (put u=0, a = -10, t = 3 above):

S = - 45m

Let the total time be T. Therefore, distance travelled in complete T seconds:

H_{1} = uT + aT^{2 }= aT^{2}

(as u = 0)

Distance travelled in (T-1) seconds:

H_{2} = u(T-1) + a(T-1)^{2 = }a(T-1)^{2}

(as u = 0)

Distance travelled in last second of its motion: H_{1} - H_{2}

_{= } a(T^{2 }- (T-1)^{2 })

^{= }a(2T -1)

Putting a = -10 and equating it to (-45) from above:

=> 5 - 10T = -45

=> 10T = 50

**T = 5 seconds**